On a new species of Diplatys Serville, 1931, from Kashmir (Dermaptera: Pygidicranidae: Diplatyniidae). - Duda, P. L.; Malhotra, Y. R. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
A new apterous species of Diplatys Serville, 1931, is described from Kaschmir. It differs from only other apterous Indian species (Diplatys imalayanus) of the genus in the number of antennal segments, prominence of pronotal sulcus, presence of pronotal corner spines, and shape size and thickness of the forceps. The name Diplatys baijali spec. nov. is proposed. Nomenclatural Actsbaijali Duda & Malhotra, 1970 (Diplatys), spec. n.